Structural and Phase Transformations in Iron-Based Alloy Obtained in Conditions of High Cooling Rate Crystallization; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Kovalevskaya Zh. G. Zhanna Gennadievna (2016, 2016)
Title screen